Social anxiety in autism spectrum disorder: A systematic review - Spain, Debbie; Sin, Jacqueline; Linder, Kai B.; McMahon, Johanna; Happé, Francesca (Research in autism spectrum disorders, 2018)
•Autism spectrum disorder (ASD) and social anxiety (SA) commonly co-occur.•Twenty-four studies have examined associations between ASD and SA symptoms.•SA, in ASD, is associated with poorer social skills, competence and social motivation.•Self-rated SA and ASD symptoms are positively correlated; parent-ratings are not.•Causal, maintaining and protective mechanisms for SA in ASD warrant investigation. Social anxiety (SA) commonly co-occurs with autism spectrum disorders (ASD). It is conceivable that inherent socio-communication impairments, or their impact on social experiences, contribute to the development of SA. We undertook a systematic review to summarise English-language research about relationships between core ASD symptoms and SA in individuals with ASD. We searched five databases for studies published up until 28 July 2017. Of 1481 publications retrieved, 24 cross-sectional studies (described in 25 papers) met the inclusion criteria. Given methodological and clinical heterogeneity, data were synthesised narratively. SA, in individuals with ASD, was associated with poorer social skills and functioning, and reduced social motivation. There were associations between self-report SA and ASD measures, but a trend towards non-significant relationships between parent-ratings of these symptoms. Tentative evidence indicated that SA symptoms were not associated with restricted, repetitive behaviours or sensory sensitivities. These findings support the notion that there are links between core ASD characteristics and SA. Further studies, employing qualitative and quantitative designs are needed to enhance understanding of causal, maintaining and protective mechanisms for SA in ASD.